Efektivitas Terapi Stimulus Kutaneus terhadap Dismenore dengan Menggunakan Olive Oil - A.Fatmawati; Yusrah Taqiyah; Fatma Jama; Wan Sulastri Emin; Nurwahyuni Munir (Window of Nursing Journal, 2025)
According to the 2018 World Health Organization (WHO), adolescents are defined as those aged 10-19 years. Adolescence in young women is marked by the onset of menstruation. However, many young women experience problems during menstruation, such as dysmenorrhea. Dysmenorrhea is abdominal pain caused by uterine contractions that occur before and during menstruation. There are two types of dysmenorrhea treatment, namely non-pharmacological and pharmacological treatment. One of the nonpharmacological treatments is cutaneous stimulus therapy. The purpose of this study was to determine the effect of cutaneous stimulation therapy using olive oil on dysmenorrhea in nursing students at the Indonesian Muslim University. This study employed a pre-experimental design with a one-group pretest and post-test. Sampling using the purposive sampling technique included as many as 30 female students who met the inclusion criteria and experienced primary dysmenorrhea. This study used the Numerical Rating Scale (NRS) pain scale. The results of this study found that before cutaneous stimulation therapy was administered, most female students experienced moderate pain levels (46.7%), and after the therapy was administered, most female students experienced mild pain levels (56.7%). The results of the statistical test using the paired T-test (p ≤ 0.05) with a p-value of 0.000 indicate that the difference is significant, so that H0 is rejected and H1 is accepted. The conclusion in this study is that there is an effect of cutaneous stimulus therapy using olive oil on dysmenorrhea in nursing students at the Indonesian Muslim University. It is expected that female students can apply cutaneous stimuli every menstrual cycle so that the intensity of dysmenorrhea can be reduced.